Analysis of Leadership, Organizational Culture, Work Facilities, and Reward Systems on Employee Performance at PT Jumaku Berjaya Sentosa - Lismayana Eryanti Siregar; Hasrul Azwar Hasibuan; Daud Arifin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aimed to analyze the effects of leadership, organizational culture, work facilities, and reward systems on employee performance at PT Jumaku Berjaya Sentosa. The research was conducted in 2026 using a quantitative approach. All 46 employees were included as respondents through a saturated sampling technique, resulting in a sample size equal to the research population. The data used were primary quantitative data obtained directly from respondents through the distribution of structured questionnaires. Data processing and analysis were carried out using SPSS version 24.0 with multiple linear regression analysis methods. The results of the analysis indicated that leadership, organizational culture, work facilities, and reward systems had positive and significant effects on employee performance, both partially and simultaneously. The regression equation obtained in this study was Y = 1.125 + 0.166X₁ + 0.272X₂ + 0.318X₃ + 0.168X₄ + e. The partial test results (t-test) showed that each independent variable had a calculated t-value greater than the t-table value with a significance level below 0.05, indicating a significant effect on employee performance. Meanwhile, the simultaneous test results (F-test) showed that the calculated F-value was greater than the F-table value with a significance level of 0.000, meaning that all independent variables jointly had a significant effect on employee performance. The work facilities variable was the most dominant factor influencing employee performance, as indicated by the largest regression coefficient and t-value. Overall, leadership, organizational culture, work facilities, and reward systems contributed 94.7% to employee performance, with a very strong relationship level indicated by a correlation coefficient value of 0.975.